Cybercrime: an encyclopedia of digital crime - Marion, Nancy E. (ABC-CLIO, 2020)
"This title has been through a marketing Launch Meeting and the information in this Transmittal form has been approved. This title has NOT been through a marketing Launch Meeting and the information in this Transmittal form has NOT been finalized"--